Migrants with a Precarious Status: Evolving Approaches of European Cities - Spencer, Sarah; Ataç, Ilker; Bastick, Zach; Homberger, Adrienne; Güntner, Simon; Kirchhoff, Maren; Mallet-Garcia, Marie (IMISCOE Research Series, 2024)
This open access book is an exploration of city responses to migrants with a precarious status in Europe. It provides new evidence and analysis from research on three cities in Austria, Germany and the UK: Vienna, Frankfurt and Cardiff. The book explores strategies and services of municipal authorities towards precarious migrants and their cooperation with non-governmental organisations (NGOs) in service provision. It focuses on healthcare, education, housing and access to advice; and particular attention is given to the situation of women.The book develops the concept of precarity in relation to migration status, and of horizontal governance arrangements within municipal authorities. It explores the tension between exclusion and inclusion of migrants who have limited rights of access to welfare services, and contributes evidence on the factors shaping municipal policy making, as well as on the framing of rationales for providing access to essential services.